Fulminant Sepsis Due to Granulibacter bethesdensis in a 4-Year-Old Boy With X-Linked Chronic Granulomatous Disease. Issue 12 (December 2017) - Mayer, Erick F.; Gialanella, Philip; Munjal, Iona; Cunningham-Rundles, Charlotte; Dara, Jasmeen
Abstract : Granulibacter bethesdensis is a Gram-negative bacillus described as a pathogen exclusively in patients with chronic granulomatous disease, a phagocytic disorder that impairs the ability to clear catalase-producing organisms. Granulibacter usually causes chronic and recurrent lymphadenopathies. We report the fatal case of a 4-year-old boy with chronic granulomatous disease, who presented with sepsis after a few days of abdominal pain and diarrhea.